Representasi Feminisme dalam Film "A Perfect Fit" (2021) - Fety Indriana (Jurnal Ilmu Komunikasi, 2022)
The drama film "A Perfect Fit" is a film that discusses a pair of lovers who are engaged and will soon be married. This marriage is a form of matchmaking between two families because one of the lovers is indebted to his lover. Based on this, the researcher wants to examine how is the representation of feminism in the film A Perfect Fit? In this study, researchers used John Fiske's semiotic theory.The findings from this study are that feminism is described through four forms, namely: women's struggle to maintain their self-esteem, women who try to deal with hegemony, women who reveal men's lies, and women's assertiveness in making decisions. From this study, researchers can provide an overview in the form of meaning, code, and signs that are in accordance with the message to be conveyed in this film.The conclusion of this study is that the form of the depiction of feminism in the Saski character depicts gender equality and the voice of expression as a woman so that the message to be conveyed about gender equality and women's rights of expression is conveyed.